SOX10 promotes the malignant biological behavior of basal-like breast cancer cells by regulating EMT process - Kai Yang; Fen Yun; Lin Shi; Xia Liu; Yong Feng Jia (Heliyon, 2023)
Background: The diagnostic utility of SRY-box transcription factor 10 (SOX10) expression in basal-like breast cancer (BLBC) has been reported previously. However, the effect of SOX10 on the malignancy of BLBC cells and the underlying molecular mechanisms remain unelucidated. Here, we investigate the regulatory mechanisms and roles of SOX10 in BLBC progression. Methods: Sequencing data from patients with BLBC were extracted from the Cancer Genome Atlas database to determine the transcriptomic levels of SOX10 across breast cancer subtypes. Subsequently, the bioinformatics relevance of SOX10 in BLBC was investigated. Immunohistochemical assays were used to corroborate the protein expression of SOX10 in clinicopathological specimens (human breast cancer paraffin tissues). RNA interference was used to downregulate SOX10 expression, and the efficiency of interference was evaluated using quantitative PCR. The expression levels of molecules related to the epithelial-mesenchymal transition (EMT) pathway were determined by western blotting. Various assays, such as transwell, colony formation, and flow apoptosis assays, were conducted to assess the malignancy of BLBC cells (MDA-MB-231). Results: Bioinformatics analyses revealed the differential expression of SOX10 in various breast cancer subtypes. An association between SOX10 and immune checkpoint expression was observed in BLBC. Additionally, immune correlation analysis indicated a positive relationship between SOX10 expression and effector immune cells. SOX10 was identified as a potential immunotherapeutic target. Juxtaposed with non-basal-like breast cancer (N-BLBC) and breast adenosis, immunohistochemical analysis revealed the upregulated expression of SOX10 in BLBC, indicating its potential diagnostic significance. Single-gene functional enrichment analysis indicated that SOX10 is associated with EMT and the tumor inflammatory index. Experimental outcomes from cellular assays suggested that the downregulation of SOX10 inhibited multiple malignancy-associated behaviors in MDA-MB-231 cells, specifically affecting the EMT process, migration, invasion, proliferation, clone formation, and anti-apoptotic activities. Conclusions: We concluded that SOX10 contributes to the malignancy of BLBC cells by modulating the EMT pathway. Moreover, we observed a notable correlation between SOX10 expression and immune responses, indicating the potential significance of SOX10 in immunotherapy.